2022
DOI: 10.3389/fpsyt.2022.806872
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder During the COVID-19 Pandemic—A Systematic Review

Abstract: BackgroundThe COVID-19 pandemic and its associated restrictions may contribute to a deterioration in mental health; individuals with obsessive-compulsive disorder (OCD) may be particularly affected. This systematic review aimed to investigate the effects of the current pandemic on people diagnosed with OCD, and whether pandemics may affect the development of OCD symptoms.MethodsWe conducted a systematic search using NCBI PubMed, SCOPUS, and Google Scholar on February 9, 2021. Research articles related to OCD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 95 publications
2
29
0
Order By: Relevance
“…The literature on the pandemic's impact on OCS is already quite extensive, including five narrative or systematic reviews: Zaccari et al (2021 , k = 14), Liu et al (2021 , k = 13), Guzick et al (2021 , k = 67), Grant et al (2022 , k = 32), and Linde et al (2022 , k = 79). Whereas the first two reviews had a narrower scope (e.g., considered only clinical samples), the latter three reviews examined OCS in general population samples and individuals with OCD during the pandemic, including both cross-sectional and longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on the pandemic's impact on OCS is already quite extensive, including five narrative or systematic reviews: Zaccari et al (2021 , k = 14), Liu et al (2021 , k = 13), Guzick et al (2021 , k = 67), Grant et al (2022 , k = 32), and Linde et al (2022 , k = 79). Whereas the first two reviews had a narrower scope (e.g., considered only clinical samples), the latter three reviews examined OCS in general population samples and individuals with OCD during the pandemic, including both cross-sectional and longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the first two reviews had a narrower scope (e.g., considered only clinical samples), the latter three reviews examined OCS in general population samples and individuals with OCD during the pandemic, including both cross-sectional and longitudinal studies. Based on their literature reviews, all three ( Guzick et al, 2021 ; Grant et al, 2022 ; Linde et al, 2022 ) argued that most (but not all) studies reported a worsening of OCS during the early stages (i.e., spring/summer 2020) of the pandemic, both in the general population and in individuals with OCD. However, the pandemic's degree of impact on OCS severity and course varied greatly between studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that SARS-CoV-2 infection increases the risk of anxiety and stress-related disorders, such as post-traumatic stress disorder (PTSD), leading to exacerbation of other psychiatric illnesses, including depression, bipolar disorder, schizophrenia, obsessive-compulsive disorder (OCD), substance abuse, and long-term cognitive decline [8][9][10][11][12][13][14]. Current studies have revealed high prevalence of depressive, anxiety, acute stress symptoms and increased COVID-19 related self-harm or suicidality in individuals with mental illness as well as an increased burden of nursing among their family members after the COVID-19 outbreak [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Obsessive-compulsive disorder (OCD) is one of the key mental health problems most affected by fear of COVID-19 (Guzick et al, 2021;Linde et al, 2022). According to the American Psychiatric Association, OCD is characterized by obsessions and compulsions.…”
mentioning
confidence: 99%